2016
DOI: 10.1016/j.exger.2015.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of mineralocorticoid receptor antagonism on vascular function in healthy older adults

Abstract: Mineralocorticoid receptor (MR) activation by aldosterone may regulate vascular function in health or contribute to vascular dysfunction in cardiovascular disease. Whether the effects are beneficial or detrimental to vascular function appear to be dependent on the integrity of the vascular endothelium and whether the responses are short-term or chronic. Acute modulation of MR activation has resulted in conflicting outcomes on vascular function in young healthy adults. Little is known about the vascular role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
0
11
0
1
Order By: Relevance
“…Ventricular–arterial coupling may also be useful to assess response to various therapeutic approaches in chronic HF. Table summarizes various therapeutic strategies having beneficial effects on VAC in HFrEF …”
Section: Ventricular–arterial Coupling In Heart Failurementioning
confidence: 99%
See 1 more Smart Citation
“…Ventricular–arterial coupling may also be useful to assess response to various therapeutic approaches in chronic HF. Table summarizes various therapeutic strategies having beneficial effects on VAC in HFrEF …”
Section: Ventricular–arterial Coupling In Heart Failurementioning
confidence: 99%
“…Eplerenone improves endothelial function and vascular compliance in HFrEF patients, while having beneficial effects on their exercise capacity, quality of life, and prognosis. Moreover, this agent exerts anti‐fibrotic action, alleviating cardiac remodelling and LV stiffness …”
Section: Ventricular–arterial Coupling In Heart Failurementioning
confidence: 99%
“…In contrast to the protective role of MR activation in brachial artery FMD observed in previous studies of healthy populations [18*,36], normotensive African-Americans developed endothelial microvascular dysfunction (evaluated by digital pulse arterial tonometry) in response to acute aldosterone administration and this was prevented by spironolactone[37*]. It was suggested that the endothelial dysfunction in healthy African-Americans may be due to decreased vascular G6PD activity in this population.…”
Section: Introductionmentioning
confidence: 77%
“…Acute and chronic MR activation in healthy men improved endothelium-dependent relaxation and enhanced NO bioactivity[17]. Accordingly, short-term MR antagonism with eplerenone impaired endothelial function in healthy older adults, as measured by brachial artery flow-mediated dilation (FMD), in association with reduced eNOS activity as determined by decreased eNOS Ser1177-phosphorylation[18*]. In another study, MR inhibition improved FMD; however, the degree of improvement correlated with increased adiposity and fasting glucose, with no effect on vasorelaxation in non-obese patients[19].…”
Section: Introductionmentioning
confidence: 99%
“…Also renal plasma flow was reduced after aldosterone infusion if the effect of the endothelium is excluded by simultaneous application of L-NMMA to inhibit NO synthase (Schmidt et al 2006). Likewise, Hwang and coworkers show that in healthy older people, acute MR antagonism impairs endothelial function by inhibiting NO formation and endotheliumdependent vasorelaxation (Hwang et al 2016). This fits well to observations made by Liu and coworkers and confirmed by Heylen and coworkers who showed that acute aldosterone application can lead to a vasodilation dependent on NO generation from the endothelium and to vasoconstriction via ROS in endothelium-denuded vessels (Liu et al 2003, Heylen et al 2009).…”
Section: Endothelial Cellsmentioning
confidence: 97%